Prenatal and Peripartum Management of Patients with Hypofibrinogenemia Resulted in Two Successful Deliveries - Yuko Teraoka; Hiroshi Miyoshi; Kumi Oshima; Satoshi Urabe; Norifumi Tanaka; Yoshiki Kudo (Hindawi Limited, 2017)
Fibrinogen is an essential agent involved in maintaining pregnancy and coagulation. Since inherited fibrinogen disorders introduce greater risks for conditions such as placental abruption and postpartum hemorrhage, careful prenatal and perinatal management is essential for this patient population. We report two cases of successful deliveries in patients with hypofibrinogenemia. Case 1 is of a 26-year-old (gravida 1, para 1) woman. The patient's fibrinogen level increased spontaneously to higher than 300 mg/dL during pregnancy, without treatment. She delivered at week 38 of gestation, with no complications. Case 2 is of a 30-year-old (gravida 3, para 1) woman. We performed repeated infusions of fibrinogen to maintain the level higher than 100 mg/dL during pregnancy and at least 200 mg/dL in the perioperative period; the patient delivered a healthy infant. We identified a new mutation, Hiroshima I (γ278Tyr→His). It is important to maintain appropriate fibrinogen levels in cases of inherited fibrinogen disorders for successful prenatal and peripartum management.